ASSESSMENT OF RISKS AND ITS ATTITUDES IN POULTRY EGG PRODUCTION AMONG POULTRY FARMERS IN KUJE AREA COUNCIL, FEDERAL CAPITAL TERRITORY, NIGERIA - Olohungbebe, Sheu Ahmad; Olawoye, Tosin; AbdulKareem, Uswat Moni (FUDMA JOURNAL OF SCIENCES, 2025)
This research assessed the risks and attitudes of poultry producers associated with poultry farmers in the Kuje area council, the federal capital territory of Nigeria. A multistage sampling technique was employed and a total of 109 farmers involved in poultry farming were randomly selected across five wards from a sample frame of 150 poultry farmers. Descriptive and inferential statistics, like Kendall's Coefficient of Concordance, were employed to find out the risk management practices adopted by the poultry egg producers in the study area. It was evident from the result that there was a moderate level of agreement (W=0.340) among the egg producers in the rankings of the risk management practices. The result of the poultry farmers' attitude towards risk using the safety-first behavioral model approach, showed that the poultry producers in the study area were risk neutral. The major types of risk that were severe and faced by the poultry producers in the study area were weather fluctuation, price of birds and infectious parasites. The study, therefore, recommends that poultry farmers should be encouraged to adopt more management practices like proper sanitation, proper disposal of dead birds and debeaking that can reduce risk generally.